Endoscopic Decompression for Haglund’s Deformity: Outcomes and Efficacy - Rajat Kapoor; Brijesh Sharma; Chandra Prakash Pal; Yashvardhan Sharma (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: Haglund’s deformity, a bony prominence on the back of the heel, can cause significant pain and functional limitations. Endoscopic decompression has emerged as a minimally invasive alternative to traditional open surgery for addressing this condition. This study aimed to evaluate the outcomes and efficacy of endoscopic decompression for Haglund’s deformity. Methodology: A prospective observational study was conducted on 30 patients with Haglund’s deformity who underwent endoscopic decompression. Preoperative assessments included clinical evaluation, radiographic imaging, and functional outcome scores (AOFAS, Maryland Foot Score, and Visual Analog Scale [VAS]). Patients were followed up at 3 weeks, 6 weeks, 3 months, 6 months, and 1 year postoperatively, with outcomes assessed using the same measures. Results: The study demonstrated significant improvements in functional outcomes and pain reduction following endoscopic decompression. AOFAS scores improved from a baseline of 62.3 to 96.3 at 6 months, and Maryland Foot Scores increased from 74.1 to 98.2. VAS pain scores decreased substantially from 7.2 to 0.8. These improvements were sustained at 1-year follow-up. No major complications were reported. Conclusion: Endoscopic decompression for Haglund’s deformity is a safe and effective procedure that provides significant pain relief and functional improvement. This minimally invasive technique offers a promising alternative to open surgery, with the potential to enhance patients’ quality of life.